The Blame Game: Stigma and HIV/AIDS in an African Metropolis - WA Akande; MM Tserere; MF Adewuyi; E Titilola Akande; BE Adetoun (Tehran University of Medical Sciences, 2011)
Background: The purpose of the present study was to explore further the cross-cultural validity, consistency, and replicability of FAIDSS among students when assessing HIV/AIDS-related stigma and fear of people living with HIV/AIDS (PLWHA) in Lagos metropolis. Methods: Using a purposive method, participants in Lagos Metropolis were surveyed using a questionnaire and conceptualization derived from the work of Ross and Hunter (1992) to measure a variety of HIV-related attitudinal and behavioural items. Quantitative data analyzed employing factor analysis using maximum-likelihood extraction followed by oblique rotation (direct oblimin, delta= 0). Results: On the factor scale measuring having fear of sex with a particular person, younger respondents especially females significantly more likely to report greater fear than for any other groups. Our findings further suggest that levels of fear of outsiders are high among males and need urgent action and intervention at both individual and societal levels. Conclusion: It is argued that messages and interventions must be targeted to promote a positive social environment for those living with or affected by HIV/AIDS, and to be useful in understanding stigma, fear and prejudice more fully and in reducing them. A crosscurrent behavioral change that can transform AIDS from an inevitably fatal pandemic to a chronic and manageable disease is the answer.